2001
DOI: 10.1192/bjp.178.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual functioning and outcome of patients with severe psychotic illness randomised to intensive case management

Abstract: ICM appears to be a cost-effective strategy for a subgroup of patients with severe psychosis with cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 31 publications
1
44
0
1
Order By: Relevance
“…After exclusion of 613 articles for various reasons (Figure 1), we included 36 RCTs (total 7 494 patients) plus an additional 14 companion reports. [61][62][63][64][65][66][67][68][69][70][71][72][73][74] The studies were published between 1987 and 2014 by researchers in North America (n = 24), Europe (n = 8), Australia (n = 2), Israel (n = 1) and South Africa (n = 1) ( Table 1). One study was a cluster RCT.…”
Section: Resultsmentioning
confidence: 99%
“…After exclusion of 613 articles for various reasons (Figure 1), we included 36 RCTs (total 7 494 patients) plus an additional 14 companion reports. [61][62][63][64][65][66][67][68][69][70][71][72][73][74] The studies were published between 1987 and 2014 by researchers in North America (n = 24), Europe (n = 8), Australia (n = 2), Israel (n = 1) and South Africa (n = 1) ( Table 1). One study was a cluster RCT.…”
Section: Resultsmentioning
confidence: 99%
“…The only randomized controlled trial that could be found comparing a novel with standard general service provision for people with ID was conducted by Hassiotis et al. (2001).…”
Section: Resultsmentioning
confidence: 99%
“…However, this is to be expected in the evaluation of complex interventions. Thus, for example, in assertive community treatment one of the robust findings from the largest of the controlled trials the UK700 Study, whose general findings were essentially negative (Burns et al, 1999) was that those with borderline intellectual disability, when treated by intensive case management spent significantly less time in hospital and also had improved quality of life and functioning, compared with those who were treated with standard treatment Hassiotis et al, 2001). In both assertive community teams, home treatment services and crisis resolutions teams, as well as with the 12-step treatment for alcoholism and many other interventions the first phase is unfortunately ignored.…”
Section: Problems Of Evaluating Interventions In Community Servicesmentioning
confidence: 99%